Observaciones sobre la periodicidad de las microfilarias de Ochoterenella en Bufo marinus de Colombia - Marinkelle, C. J. (1968)
A total of 1 032 toads (Bufo marinus) were examined for the presence of microfilariae (Mf.). Toads known to harbour Mf. were examined between 1 0 AM and 4 PM (177 individuals), and between 10 PM and 1 AM (57 in dividuals). The number of Mf. found per mI of blood, compared with the number of adult females recovered from the dissected toads, showed that less Mf. were present in the heart blood at night than at day time. It was al so found that when more than the average number of females were present, less Mf. were found in the peripheral blood (calculated per recovered female). Toads bled 6 times during the day and 6 times at night for a period of 38 days also showed that significantIy less Mf. were present in the night blood. Experiments showed that neither muscular and respiratory activity, nor tem perature influenced the Mf. density in the blood during the day or at night.This is the first report of Mf. periodicity in amphibians and the second on Mf. periodicity of species belonging to the subfamily Onchocercinae, to which the genera Wunchereria, Onchocerca and Dipetalonema also belong.